Improving the Mechanical Properties of Epoxy by Adding Sub-micron Cantaloupe Peel Fibers - Lutfi, Rand B.; Jassim, Widad H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The use of bio-fruit waste has more attention in recent years because of the low cost of bio-fibers and the protection of the environment. In this study, the epoxy was reinforced with fruit residues (cantaloupe peel powder) in proportions (1%, 2%, 3%, 4%, 5%, 7.5%, and 10% by weight) as results of mechanical tests such as impact, hardness, flexural and compression. Adding sub microns particle size cantaloupe peels particles with a weight ratio of 7.5% improves the epoxy mechanical properties, like impact strength, hardness, flexural strength, and compression strength by 59.43%, 5.8%, 45.7%, and 118.2%, respectively. Using X-ray diffraction, the crystallite size ( D) of cantaloupe peel the powder was about (3 nm). In this research, Scanning electron microscopy was used to examine the morphology of the (epoxy/7.5 % cantaloupe peel powder) composite and to interpret the improvement in epoxy mechanical properties.